2022
DOI: 10.3390/ijerph191811376
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution Characteristics and Source Analysis in the Dust Fall on Buildings of Different Heights

Abstract: High-rise buildings block airflow, and dust accumulates on their upper surfaces. In this study, dust fall on the rooftops of low-, medium-, and high-rise buildings was sampled and analyzed to assess the degree of atmospheric heavy metal pollution. The Cr, Mn, Ni, Cu, Zn, As, Cd, and Pb mass fractions in dust samples were analyzed by microwave digestion/inductively coupled plasma-mass spectrometry. The average Cr, Ni, Cu, As, Cd, and Pb concentrations were highest on the rooftops of low-rise buildings, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…PCA showed that the contribution rate of principal component 1 of the dump was 45.74%, and the main contributing elements were Cu, Cr, Ni, Pb, As and Zn. Among them, Cr, Zn, Ni and Cu are derived from the wear on tires and other automobile parts [ 51 ], and Pb is caused by automobile exhaust pollution [ 52 ]. As is caused by fuel combustion and atmospheric deposition from nearby factories [ 53 ]; it is identified as both a traffic source and an industrial source.…”
Section: Discussionmentioning
confidence: 99%
“…PCA showed that the contribution rate of principal component 1 of the dump was 45.74%, and the main contributing elements were Cu, Cr, Ni, Pb, As and Zn. Among them, Cr, Zn, Ni and Cu are derived from the wear on tires and other automobile parts [ 51 ], and Pb is caused by automobile exhaust pollution [ 52 ]. As is caused by fuel combustion and atmospheric deposition from nearby factories [ 53 ]; it is identified as both a traffic source and an industrial source.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies focused only on the impact of construction activities on groundwater , and the neighboring soil environment. , However, with the increasing awareness of environmental protection, the dust pollution caused by construction is gradually being recognized by more and more people . A complete construction process generates a large amount of dust, mainly fine particles, with particles less than 10 μm in diameter accounting for about 90% of the total emissions . The generation of these fine particles not only significantly reduces the quality of the surrounding air but can also cause damage to equipment and shorten its service life. , Moreover, these particles have the potential to enter the human body through inhalation, thereby disrupting gas exchange within the lungs and increasing the transmission of respiratory diseases .…”
Section: Introductionmentioning
confidence: 99%
“… 6 A complete construction process generates a large amount of dust, mainly fine particles, with particles less than 10 μm in diameter accounting for about 90% of the total emissions. 7 The generation of these fine particles not only significantly reduces the quality of the surrounding air but can also cause damage to equipment and shorten its service life. 8 , 9 Moreover, these particles have the potential to enter the human body through inhalation, thereby disrupting gas exchange within the lungs and increasing the transmission of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%